Defining critical success factors in TOD implementation using rough set analysis - Thomas, Ren; Bertolini, Luca (Journal of Transport and Land Use, 2015)
This paper defines critical success conditions in transit-oriented development (TOD), evaluating the impact of practices, policies, and governance models on implementation. As part of a meta-analysis of 11 international case studies, 16 critical success factors were developed and validated using rough set analysis. The results show that political stability at the national level, relationships between actors in the region, interdisciplinary teams used to implement TOD, and public participation are the most significant success factors in TOD implementation. The set of decision rules reveals that several combinations of critical success factors have been effective in achieving implementation across city-regions in different contexts.